2020
DOI: 10.1038/s41419-020-02951-7
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 conditional deletion attenuates retinal ganglion cell apoptosis by accelerating autophagic flux in a mouse model of chronic ocular hypertension

Abstract: Autophagy has a fundamental role in maintaining cell homeostasis. Although autophagy has been implicated in glaucomatous pathology, how it regulates retinal ganglion cell (RGC) injury is largely unknown. In the present work, we found that biphasic autophagy in RGCs occurred in a mouse model of chronic ocular hypertension (COH), accompanied by activation of Rac1, a member of the Rho family. Rac1 conditional knockout (Rac1 cKO) in RGCs attenuated RGC apoptosis, in addition to blocking the increase in the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…We first examined the dynamic changes of Müller cell and microglia activation in the mouse model of COH that was produced by injecting micro-magnetic beads into the anterior chamber [ 12 , 13 ]. Changes of IOP in COH mice are shown in Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first examined the dynamic changes of Müller cell and microglia activation in the mouse model of COH that was produced by injecting micro-magnetic beads into the anterior chamber [ 12 , 13 ]. Changes of IOP in COH mice are shown in Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse COH model was produced by injection of the micro-magnetic beads (2 μL, diameter ≈ 10 μm, BioMag ® Superparamagnetic Iron Oxide, Bangs Laboratories, Ins, USA) into the anterior chamber of the right eyes, referring to the procedure previously described in detail [ 12 , 13 ]. In brief, the mice were anesthetized by 2% pentobarbital sodium (40 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Thereby, it would be predictable that the autophagic flux have a relevant role during initial stages of the stimulus, until the cell reach a stable metabolic state. Prolonged exposition frequently show a different autophagy flux ( Zhang et al, 2020 ). By Western blot and immunofluorescence assays we demonstrated that autophagic flux returned to normoxic levels when incubated in 1% O 2 during 24 h. This result indicates that the activation of the flux is transient and takes place immediately after the exposition to hypoxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine (CQ) and hydroxychloroquine (HCQ) are autophagic inhibitors popularly used as antitumor agents [ 241 ]. Both CQ and HCQ have been reported to cause RGC damage [ 242 , 243 ]. In the clinic, the mean values of quantified fundus autofluorescence (QAF, an indirect approach to measuring lipofuscin in the RPE in vivo) were significantly higher in patients receiving CQ/HCQ than in healthy controls, indicating that CQ/HCQ treatment leads to retinal damage [ 244 ].…”
Section: Effects Of Autophagic Inducers and Inhibitors On Retinal Degenerative Diseasesmentioning
confidence: 99%